Tatyana Larina’s Letter from Onegin’s Perspective - Greenbaum, Oleg (Respectus Philologicus, 2013)
This paper considers some issues of the rhythmical semantic analysis of the text of the letter written by Tatyana Larina, presented in the third chapter of A. S. Pushkin’s novel Eugene Onegin. Previous work in this area has been devoted to studying the structural and compositional peculiarities of the text, as well as to rhythmical and expressive aspects of the reader’s perception of Tatyana’s letter. The present study continues the selected method of analysis in a way related to the specific nature of this letter: the fragment of the novel is viewed as a separate text “inserted” into the whole, which can and should be read separately from the general course of the poetic narrative. The chosen approach allows us to examine the process of perception of Tatyana’s letter by the addressee, Onegin, and, at the same time, makes it possible to clarify Pushkin’s reasons for hiding the text of the letter from readers for so long, as though looking for the best time and place to present it. The study shows that the method of reading Tatyana’s letter as “separate” reveals that at the centre of the emotionally expressive perception of this text is the word “hope.” This fact helps to yield new evidence pointing to the reasons for Onegin’s ruthless and seemingly inadequate response to Larina’s letter.